A study of Chinese consumers' online purchase intention based on Technology Acceptance Model and perceived risk - Zhao, Hanyi (2022)
The widespread use of the Internet has promoted the development of ecommerce and electronic markets all around the world. The number of Internet users has increased rapidly in recent years, but the development of online shopping in China is not as good as expected. Hence, it is necessary to investigate the factors that impact Chinese consumers’ online shopping behavior. Consumers’ personal characteristics and perceived risks of online shopping are regarded as important influencing factors, as they may directly and indirectly influence consumers’ online purchasing behavior. However, few previous studies focused on investigating whether these factors impact Chinese consumers’ online shopping behavior simultaneously based on a reliable model. To analyze the impact that perceived risk in online shopping and characteristics has on the Chinese consumers’ online shopping behavior, the study develops an Extended Technology Acceptance Model that contains six dimensions of perceived risk, including social risk, psychological risk, performance risk, time risk, privacy risk, and financial risk, and three characteristics, which are gender, age, and the length of time on the Internet every week. The empirical analysis based on the results of 271 valid questionnaires show that perceived ease of use positively impacts perceived usefulness and attitude towards shopping online, perceived usefulness has a positive impact on attitude and intention to shop online, and attitude also positive influences shopping online intention. Regarding the perceived risk, six dimensions of it negatively impact perceived usefulness, attitude, and intention. Besides, it can be found that gender shows differences in perceived ease of use, perceived usefulness, social risk, and time risk. People who spend different time online every week vary in perceiving perceived usefulness, social risk, privacy risk, and performance risk. People of different ages perceive different levels of perceived usefulness, privacy risk, time risk, and financial risk. Furthermore, the study also provides Chinese online stores and relevant organizations with management implications and recommendations.